KESESUAIAN (FIT) ANTARA LINGKUNGAN DENGAN ORIENTASI STRATEGI UNTUK MENINGKATKAN KINERJA USAHA KECIL MENENGAH (UKM): SEBUAH MODEL PENGEMBANGAN TEORITIS - Suliyanto, Suliyanto (Performance, 2009)
Research on the orientation of the strategy with the environment have been carried out by previous researchers, but still produces a variety of findings, in addition to the research is generally done in large companies. Therefore, research on strategic orientation fit and environment in small and medium-sized companies that use environmental typology of Dess and Beard, (1984) still needs to be done.